2021
DOI: 10.3390/w13050634
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Climate Warming on Lake Surface Heat Exchange and Ice Phenology of Different Types of Lakes on the Tibetan Plateau

Abstract: Increasing air temperature is a significant feature of climate warming, and is cause for some concern, particularly on the Tibetan Plateau (TP). A lack of observations means that the impact of rising air temperatures on TP lakes has received little attention. Lake surfaces play a unique role in determining local and regional climate. This study analyzed the effect of increasing air temperature on lake surface temperature (LST), latent heat flux (LE), sensible heat flux (H), and ice phenology at Lake Nam Co and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Hence, experiments (SenExp_u*) with u* multiplied by a series of scale factors (varies from 1.2 to 2.0 with a 0.2 interval) were conducted to analyze the sensitivity of water temperature to u*. Previous studies have shown that the white ice albedo (α max ) is a key parameter that determines lake ice phenology [65,66]. Thus, a series of sensitive experiments with changed white ice albedo (from 0.2 to 0.6 with a 0.05 interval) were conducted to explore its influence on ice phenology and water temperature.…”
Section: Experimental Designmentioning
confidence: 99%
“…Hence, experiments (SenExp_u*) with u* multiplied by a series of scale factors (varies from 1.2 to 2.0 with a 0.2 interval) were conducted to analyze the sensitivity of water temperature to u*. Previous studies have shown that the white ice albedo (α max ) is a key parameter that determines lake ice phenology [65,66]. Thus, a series of sensitive experiments with changed white ice albedo (from 0.2 to 0.6 with a 0.05 interval) were conducted to explore its influence on ice phenology and water temperature.…”
Section: Experimental Designmentioning
confidence: 99%
“…Furthermore, a small bias on the air temperature could change the temperature evolution of the lake and then influence the lake ice phenology (Bernus & Ottlé, 2022). The lack of in situ observations at TP alpine lakes has made the simulation of lake thermal structure and lake ice formation more difficult and uncertain (Huang et al., 2017; Lang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The TP preserves a sufficient amount of lakes and glaciers, which are both experiencing hydrological change in the context of climate warming. The surface processes and ice phenology of lakes on the TP were investigated by Lang et al (2021) [11], and an increasing trend in lake surface temperature and latent heat flux, as well as a decreasing trend in sensible heat flux and ice thickness, were illustrated. Based on surface mass balance parameterizations, the mean glacier volume loss of Da Anglong Glacier during 2016-2098 was simulated by Zhao et al (2022) [12] to be 38% and 83% of the volume in 2016 under RCP2.6 and RCP8.…”
mentioning
confidence: 99%